2020
DOI: 10.1093/ijlct/ctaa018
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties of sonicated graphene in coconut oil as a phase change material for energy storage in building applications1

Abstract: This study aims to investigate the thermal properties of a phase change material (PCM) based on coconut oil for building energy storage applications. Coconut oil is classified as an organic PCM composed of fatty acids made from renewable feedstock. However, low thermal conductivity is one of the major drawbacks of organic PCMs that must be improved. Graphene could be an effective material to enhance the thermal performance of organic PCMs. In this study, coconut oil with a latent heat capacity of 114.6 J/g and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Compared to CO-CA eutectic PCMs, the increment in thermal conductivity of CO-CA-G varied from 3-21.7% with respect to the graphene content. The findings in this study are consistent with the findings by Safira et al [8], which found that the thermal conductivity of coconut oil with graphene increased with the increase in graphene concentrations. The high thermal conductivity of graphene and Brownian motion contribute to the increase in the thermal conductivity of the eutectic mixture [9].…”
Section: Thermal Conductivitysupporting
confidence: 93%
See 2 more Smart Citations
“…Compared to CO-CA eutectic PCMs, the increment in thermal conductivity of CO-CA-G varied from 3-21.7% with respect to the graphene content. The findings in this study are consistent with the findings by Safira et al [8], which found that the thermal conductivity of coconut oil with graphene increased with the increase in graphene concentrations. The high thermal conductivity of graphene and Brownian motion contribute to the increase in the thermal conductivity of the eutectic mixture [9].…”
Section: Thermal Conductivitysupporting
confidence: 93%
“…In addition, they usually could be recovered from abundant underused feedstock and are available at low cost [5]. Bio-resourced plant oil such as coconut oil [6], palm kernel oil, Allanblackia, shea butter [7], vegetable fat [5], and beef tallow [8] have also been used as PCMs. Kahwaji and White [9] reported that coconut oil is thermally and chemically stable with acceptable latent heat and melting temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In year 2020, it was found that when combined with sonicated graphene, coconut oil can serve as a phase change material for energy storage purposes. It was found that the best results for this application may be obtained at low concentrations of graphene at 0.3 wt% graphene [ 76 ]. In recent year, Lugoda found that combining coconut oil and carbon black, a strain sensor can be developed.…”
Section: Application Of Coconut Oilmentioning
confidence: 99%
“…Safira et al prepared a composite PCM that used coconut oil as PCM and sonicating graphene as thermal conductivity enhancer. Through the test fount that, when the addition amount of sonicating graphene was 0.3 wt.%, its thermal conductivity was increased by 69% compared with pure PCM [20]. Lin et al prepared the palmitic acid (PA)/nanosilica composite PCM with the optimum mass ratio of 70:30, the latent heat of melting (Hm) and the melting temperature (Tm) were 128.42 J/g and 60 ℃, respectively.…”
Section: Introductionmentioning
confidence: 99%